2018
DOI: 10.1111/jdi.12817
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of seasonal administration on the efficacy of sitagliptin: Subanalysis of the Januvia Multicenter Prospective Trial in Type 2 Diabetes Study

Abstract: Aims/IntroductionHemoglobin A1c (HbA1c) levels in patients with type 2 diabetes mellitus fluctuate throughout the year. However, there are few studies that have evaluated the therapeutic effect of hypoglycemic agents while considering such fluctuations. In a multicenter study (Januvia Multicenter Prospective Trial in Type 2 Diabetes Study), pretreatment patients with type 2 diabetes mellitus were divided into seven groups and given sitagliptin for 1 year. The aim of the present study was to evaluate the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…There is a report that blood glucose levels fluctuate with the season and HbA1c levels are high in the winter and low in the summer [33][34][35][36][37]. The same has been described in reports on drug effectiveness [38,39]. It is still possible that the season from April to July has an effect.…”
Section: Discussionmentioning
confidence: 86%
“…There is a report that blood glucose levels fluctuate with the season and HbA1c levels are high in the winter and low in the summer [33][34][35][36][37]. The same has been described in reports on drug effectiveness [38,39]. It is still possible that the season from April to July has an effect.…”
Section: Discussionmentioning
confidence: 86%
“…Sakura et al have reported on seasonal variation in the effect of sitagliptin in patients who were not using insulin concomitantly [7]. The present study followed their scheme for grouping patients.…”
Section: Discussionmentioning
confidence: 94%
“…HbA1c was most frequently reported to reach its highest level in March in Japan [1,2,4] and its lowest level in August to October [1][2][3][4]. Therefore, patients were divided into four groups based on the period in which sitagliptin was started: group 1 (in February to April), group 2 (in May to July), group 3 (in August to October), and group 4 (in November to January of the following year), which is the same as previously described [7]. Then changes in HbA1c and BMI at 1, 3, 6, 9, and 12 months from baseline, which was the first day of sitagliptin administration, were compared within each group and among the groups.…”
Section: Endpointsmentioning
confidence: 95%
See 2 more Smart Citations